(untitled) (Biological Sciences - PJSIR, 2025)
Inflammatory bowel disease develops in areas of the world where prebiotic intake is inadequate. Ulcerative colitis is a type of IBD symbolized by inflammation of the colon’s mucosal lining. increased consumption of DF is linked to a decreased risk of inflammation. Anaerobic colonic bacteria transform prebiotics into short chain fatty acids. Okara is an emerging prebiotic derived from agro-food industrial waste that enhances human gut health. The current research was conducted to utilize nutrient rich residue Okara for the preparation of value added products in different proportions 0, 5, 10, 15 and 20% against GIT disorder. The severity of colitis was made less severe by Okara as seen by the lowering pH and decreased disease activity index. Short chain fatty acids values significantly (P<0.05) increase in both studies. Okara an agro-industrial waste helps to support the species of bacteria in the gut that make short-chain fatty acids and provide anti-inflammatory potentials. These patterns might encourage better gut health.